The Eternal River of Knowledge: Flow and Modern Relevance of the Indian Knowledge System - Khan, Hafizur Rahman (Journal of Innovation in Education and Social Research, 2025)
The Indian Knowledge System (IKS) represents a vast and intricate corpus of intellectual inquiry that has flowed contiguously for millennia. Often misrepresented in the West as solely spiritual or mystical, IKS is, in fact, a sophisticated framework of epistemology (Pramana), ontology, and axiology that addressed diverse fields from mathematics and astronomy to medicine, linguistics, and political economy. This article argues that the IKS is not a relic of the past but a dynamic "eternal river" whose waters hold profound relevance for addressing contemporary global challenges. By examining its foundational principles—such as the pursuit of holistic knowledge, ecological consciousness embedded in texts like the Vedas and Upanishads, and the logical-empirical frameworks of schools like Nyaya and Vaisheshika—we demonstrate how IKS offers corrective insights to the fragmentation of modern disciplines, environmental crises, and the limitations of purely materialist paradigms. This paper synthesizes key concepts from primary sources and secondary scholarship to posit that engaging with IKS is essential for fostering a more inclusive, sustainable, and integrated global knowledge ecology.